Kierunki zastosowania wizualizacji informacji w systemach business intelligence - Dudycz, Helena (The basic directions of using visualization of information in business intelligence systems, 2005)
The article presents the most important trends of visualization of information in business intelligence systems. In the beginning the author describes the concept of business intelligence to support decision-making. Then the requirements of management in relation to economic reports are presented. The last part of the article introduces the possibilities of using visualization in business intelligence systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 199-213